Development of Indonesian Sign Language System (SIBI) Dictionary Application for Students with Special Needs - Syamsuddin Syamsuddin; Triyanto Pristiwaluyo; Wizerti A Saleh; Zulfitrah Zulfitrah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The process of communication for deaf persons needs to be facilitated by a particular language. Friends who are deaf want language that is appropriate for everyday requirements in order to communicate and comprehend communications. The objectives of developing assistive technology for the Indonesian Sign Language System (SIBI) dictionary application are to optimize services, create friendly assistive technology, improve the language skills of students with hearing impairments by utilizing technology, and create an inclusive campus that is friendly for students with special needs. The model used in research and development (RD) is Borg Gall. The development stage of the SIBI dictionary application goes through 10 stages, from collecting vocabulary information to the resulting product in the form of an application embedded on a smartphone. Product testing was carried out in two stages to identify constraints in the application and use of the available features. The population was 17 students with special needs at various semester levels, including eight students with hearing impairments (deaf), students with visual impairment (blind/low vision) as many as eight students, then there is one student with obstacles to the function of mobility. The results of this study are that the SIBI Dictionary Application is a dictionary in the form of sign language videos equipped with sound and text as well as word meanings. The video also has a tutorial. This tool can help hearing-impaired pupils study after utilising a digital dictionary. Increasing hearing-impaired kids' vocabularies (value indicator assessment). Deaf community "GERKATIN" and special education students. Thus, the SIBI Dictionary Application with sign language movies with sound, text, and word definitions can better aid kids with special needs and can be downloaded from smartphone app services. All UNM students receive volunteer instruction from special needs classmates.